Methods of Synthesis of Quasi - Balanced Circuits for Measuring of Impedance Components - Cichy, Adam (Elektronika ir Elektrotechnika, 2016)
Quasi-balanced circuits are not widely known and often built. This is mainly due to insufficient knowledge of their properties. Meanwhile, these systems have properties which may be their great advantages. Quasi-balanced circuits have a maximum convergence, allowing the full independent quasi-balancing for each of the components. Although the simple quasi-balanced circuits enable the measurement of a single component, but there are solutions which allow the measurement of the impedance of the two components at the same time. The article presents two methods of the synthesis of quasi-balanced circuits, which are different in approach. The first method is based on a linear model of the transducer, the other on the analysis of the measuring signals of quasi-balanced bridges. Virtual instrument was implemented and the results of measurements of selected elements were compared with results from other device. This confirms the usefulness of the method. DOI: http://dx.doi.org/10.5755/j01.eie.22.2.6463